Crossing the (Wallace) line: local abundance and distribution of mammals across biogeographic barriers - Brodie, Jedediah F.; Helmy, Olga E.; Pangau-Adam, Margaretha Z; Ugiek, Giyarto; Froese, Graden Z.L.; Granados, Alys; Mohd. Azlan, Jayasilan (Blackwell Publishing Ltd, 2018)
Past and ongoing vertebrate introductions threaten to rearrange ecological communities in the Indo-Malay Archipelago, one of Earth's most biodiverse regions. But the consequences of these translocations are difficult to predict. We compared local abundance and distributions in four tropical mammal lineages that have crossed from Asia to Wallacea or New Guinea. The local abundance of macaques (Macaca spp.), which naturally crossed Wallace's Line, was higher in Sulawesi (east of the line; mean = 3.7 individuals per camera station, 95% CI = 2.2: 5.1) than in Borneo (west of the line; mean = 1.1, CI = 0.8: 1.4), but the local abundance of Malay civets (Viverra tangalunga), Rusa deer, and Sus pigs was similar in their native ranges and where they had been introduced by humans east of Wallace's Line. Proximity to rivers increased Malay Civet local abundance and decreased the local abundance of pigs in parts of their introduced ranges (Maluku and New Guinea, respectively), while having no effect on local abundance in their native ranges (Borneo) or other areas where they have been introduced (Sulawesi). That local abundance was higher east of Wallace's Line in just one of four mammal lineages is consistent with findings from plant invasions, where most species have similar abundance in their native and introduced ranges. However, species’ ecology may change as they enter new communities, for example, their patterns of abundance at local scales. This could make it difficult to predict community structure in the face of ongoing species introductions. © 2017 The Association for Tropical Biology and Conservation